Characterization of the volatile compound profile of artisanal Minas cheese from different regions - DÁRGERE, Adélia Ferreira; PINTO, Sandra Maria; BATISTA, Diogo Santos; CORREIA, Laryssa Fernandes; MARÇAL, Joanna Oliveira; LIMA, Lidiany Mendonça Zacaroni; FARIA, Peter Bitencourt (Food Science and Technology, 2023)
Artisanal Minas cheese (AMC) is a product with great economic, historical, and cultural value, and the final organoleptic characteristics of AMC can be influenced by soil and climate factors at the production site (terroir). This study aimed to evaluate the profile of volatile compounds in cheeses from seven certified producing regions in Minas Gerais, Brazil, to characterize the volatile compounds according to their origin. A total of 78 samples were obtained from producers registered with the health certification body (Instituto Mineiro de Agropecuária), and the health requirements, minimum ripening time, and characteristic production methods of the cheeses from each region were followed. In general, a total of 166 compounds were identified, which were divided into several chemical groups, including aldehydes (20), ketones (17), carboxylic acids (20), terpenes (6), esters (57), hydrocarbons (15), and alcohols (31). The terpenes α-pinene and caryophyllene-oxide were possible plant markers for cheeses from the Canastra and Serro regions, as these compounds were not identified in cheeses from the other regions. For cheeses from different regions, interactions between some origin-related compounds were verified, which may help establish guidelines and standards for chemical compounds at different production sites, as there are differences between the profiles of volatile compounds and the region.